PERSEPSI GURU FIQIH TENTANG KONSEP MERDEKA BELAJAR PADA KELAS X DI MAN 2 POLEWALI MANDAR KECAMATAN MATAKALI KABUPATEN POLEWALI MANDAR - Nurzamsinar; Sudirman; Widya Astrina (Universitas Islam Negeri Alauddin Makassar, 2023)
The aim of this research is to: (1) determine the perception of fiqh teachers regarding the concept of independent learning in class Matakali, Polewali Mandar Regency. This research is qualitative research that builds meaning based on field data. This qualitative research procedure produces participant descriptive data in the form of written or spoken words from people and observable behavior. Data collection was carried out by conducting observations, in-depth interviews and documentation. Data analysis is carried out by giving meaning to the data that has been collected, and conclusions are drawn from this data. Indicators of success in this research are: (1) the perception of fiqh teachers regarding the concept of independent learning in class Mandar, Matakali District, Polewali Mandar Regency. The results obtained in this research are that the concept of independent learning received a very good response and they were very enthusiastic in implementing the independent learning curriculum which provides learning freedom to students and teaching freedom to teachers. The obstacle for teachers at MAN 2 Polewali Mandar regarding the concept of independent learning is the lack of training received by teachers so that teachers' understanding of the independent learning curriculum is very small. The results of the research explain the importance of socialization, seminars and the like regarding implementing the learning curriculum so that the implementation of the curriculum runs well